Instilling Moral Education Values Through Scouting and Its Significance to Islamic Teachings - Farantika, Dessy; Purwaningrum, devia; Farida, Nikmatin Lana; Shofwan, Arif Muzayin (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
The moral education values ​​contained in scouting are apparently significant with Islamic teachings. This qualitative descriptive research using literature studies explores the moral foundations and values ​​of scouting and their significance to Islamic teachings. The data analysis technique is by sorting the data according to the research objectives. This research found the following two things. First, the ideal basis for scouting is Pancasila, the constitutional basis for scouting is the 1945 Constitution, especially article 31 paragraph 1 and Presidential Decree No. 238 of 1961. Second, the moral education values ​​contained in scouting activities are piety to God Almighty, which is significant in QS. Al-Baqarah: 3-4, QS. Al-Hujurat: 13, and QS. Ali Imran: 102; love of nature and compassion for fellow humans are significant to QS. Al-Baqarah: 29, QS. Al-Hujurat: 10, and QS. Ar-Rum: 41; polite patriot and significant knight with QS. Surah Ibrahim: 35 and QS. Lukman: 6; obedient and likes to have significant discussions with QS. An-Nisa: 59 and QS. Ali Imran: 159; willing to help and steadfast significantly with QS. Al-Maidah: 2, QS. Al-Baqarah: 153, and QS. Al-Baqarah: 155; diligent, skilled and significantly happy with QS. An-Najm: 39 and QS. Al-Insyirah: 5-6; frugal, careful, and modest are significant with QS. Al-A'raf: 31 and QS. At-Takasur: 2-3; disciplined, brave, and significantly loyal to QS. An-Nur: 64; responsible and can be trusted significantly with QS. Al-Mukminun: 8, QS. Al-Ahzab: 72, and QS. Al-An'am: 164; holy in thoughts, words and deeds significant to the QS. Al-Hujurat: 12 and QS. Al-Ahzab: 58